Gambaran Kepatuhan Mengonsumsi Tablet Fe Dengan Kejadian Stunting (Study Literature) - Hariati, Andi; Arfah, Andi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Stunting in toddlers is one of the global nutritional problems faced by people in the world. The prevalence of blockage in Indonesia is 30.8%. This study aims to find out the compliance status of pregnant women in taking fend tablets with stunting in toddlers. This research method uses a type of research literature. Search journals use accredited journal sites such as PubMed, Google Scholar and Research Gate. Based on the literature review results in 10 journals examined, it can be concluded that there is a family relationship and family support with stunting.